2019
DOI: 10.1080/02670836.2018.1463613
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of medium manganese steel through cold-rolling and intercritical annealing or warm-rolling

Abstract: Medium manganese steel is typically fabricated from hot-rolling followed by cold-rolling and intercritical annealing processes. However, a singular process, warm-rolling, is an appealing prospect. The microstructure, mechanical properties and texture of a 8 wt-% Mn–0.08 wt-% C steel was investigated by cold-rolling followed by intercritical annealing or warm-rolling. The product from both processes exhibited a highly refined microstructure as well as a large volume fraction of austenite. However, a slightly la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…As shown in Figure 9, the partitioning of C and Mn to austenite during warm rolling was confirmed, implying that the austenite with higher stability can resist severe deformation. Such warm rolling-induced partitioning was also reported by Magalhães et al [11,12]. It is worth noting that, at a higher working temperature above Ac 3 , hot rolling fails to facilitate the enrichment of austenite stabilizers in austenite by partitioning, owing to the formation of a single-phase austenite microstructure during rolling, which serves as an explanation for the lower stability of the austenite originating from hot rolling and the massive martensite transformation during subsequent cooling, as mentioned above.…”
Section: Influencing Factors Of Chemical Composition and Processing On The Austenite Reversion In Mmnssupporting
confidence: 69%
See 1 more Smart Citation
“…As shown in Figure 9, the partitioning of C and Mn to austenite during warm rolling was confirmed, implying that the austenite with higher stability can resist severe deformation. Such warm rolling-induced partitioning was also reported by Magalhães et al [11,12]. It is worth noting that, at a higher working temperature above Ac 3 , hot rolling fails to facilitate the enrichment of austenite stabilizers in austenite by partitioning, owing to the formation of a single-phase austenite microstructure during rolling, which serves as an explanation for the lower stability of the austenite originating from hot rolling and the massive martensite transformation during subsequent cooling, as mentioned above.…”
Section: Influencing Factors Of Chemical Composition and Processing On The Austenite Reversion In Mmnssupporting
confidence: 69%
“…The microstructure produced by warm rolling can result in the desired mechanical properties in MMnS. In the analysis of MMnS by Magalhães et al [12], a Fe-0.086C-8Mn-0.14Si MMnS ingot was subjected to the processing routes of "cold rolling + intercritical annealing" and "warm rolling". It was shown that although both processes exhibited refined microstructures, warm rolling offered a slightly more significant volume fraction of austenite (34 vol.%) compared with the intercritical annealed specimen (29 vol.%), which accounted for the desirable higher work-hardening rate.…”
Section: Introductionmentioning
confidence: 99%
“…In the deformation process, the metastable austenite exhibits a transformation-induced plasticity (TRIP) effect or a twinning-induced plasticity (TWIP) effect, which gives the medium-Mn steel excellent plasticity without sacrificing strength. This allows the material to meet the processing requirement for automobile parts with complex structures [5,6,7,8]. Therefore, the amount of retained austenitein medium-Mn steels determine show extensive is the TRIP effect; that is, the transformation of retained austenite into martensite during deformation increases the strength and ductility of steel simultaneously [1,2,3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the product of UTS and TE of approximately 25,000 MPa% is achievable. These steels will be used in the near future mainly as a side and anti-intrusion car body reinforcement structures (A, B, and C pillars, fenders, etc.,) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%